Seedling growth of Cordia trichotoma subjected to different sources and doses of fertilizers - Cunha, Fernanda Leite; Santos, Juscelina Arcanjo dos; Diniz, Paloma Carvalho; Melo, Lucas Amaral de; Venturin, Nelson (Revista de Ciências Agroveterinárias, 2023)
Cordia trichotoma is a species of great economic interest, however information on its nutritional requirement is still incipiente. Thus, the objective was to evaluate the efficiency and adequate doses of different sources of fertilizers, for the production of Cordia trichotoma seedlings. The experiment was conducted in a completely randomized design (DIC), in a 3 x 5 factorial, with three different sources of fertilizers, two slow-release fertilizers (ALL1 and ALL2) and the use of readily soluble sources (MAP and KCl). The second factor represents the tested doses 0, 50, 100, 150 and 200%, in relation to a dose considered standard. The doses of the slow-release fertilizer were based on the standard dose of 0.44 g seedlings-1, while the readily soluble fertilizer doses were of a fixed dose of 0.08 g seedlings-1 of KCl, and increasing doses of MAP, based on the standard dose of 0.1 g changes -1. At 270 days after sowing, the variables height, collecting diameter, dry mass and Dickson's Quality Index were measured. For each variable, the maximum technical efficiency dose (DMET) was calculated. The use of MAP and KCl provided superior growth of seedlings in relation to ALL sources, for all variables evaluated. The DMET found for ALL1, ALL2 and MAP and KCl were 200%, 200% and 120%, respectively. Thus, it is recommended to use MAP and KCl, at a dose of 120%, that is, 0.08 g L-1 of KCl and 0.12 g L-1 of MAP for fertilization of Cordia trichotoma seedlings.